2015
DOI: 10.1111/1750-3841.12939
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH and Temperature on Cabbage Volatiles During Storage

Abstract: During storage of shredded cabbage, characteristic sulfurous volatile compounds are formed affecting cabbage aroma both negatively and positively. Selected ion flow tube-mass spectrometry (SIFT-MS) was used to measure the concentration of cabbage volatiles during storage. The volatile levels of cabbage samples were measured at pH 3.3 to 7.4 at 4 °C for 14 d, and pH 3.3 at 25 °C for 5 d in order to determine the effect of pH and temperature. Aroma intensity, best aroma, freshness, and off odor were evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…SIFT-MS is suitable for online monitoring of the major VOCs emitted from plant leaves (Smith and Španěl, 2011; Amelynck et al, 2013; Akpolat and Barringer, 2015). It can be used in different ionization modes (H 3 O + , NO + , or O 2 + ), allowing different qualitative applications.…”
Section: Methodsmentioning
confidence: 99%
“…SIFT-MS is suitable for online monitoring of the major VOCs emitted from plant leaves (Smith and Španěl, 2011; Amelynck et al, 2013; Akpolat and Barringer, 2015). It can be used in different ionization modes (H 3 O + , NO + , or O 2 + ), allowing different qualitative applications.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some food VOC profiling studies are worth mentioning, and improvement of the sensitivity in instruments with reduced size and cost will certainly open new opportunities . Thus, monitoring of processes or storage conditions during shelf life of various foodstuffs was undertaken with SIFT‐MS instruments: cocoa roasting, beef under modified atmosphere packaging, chemical spoilage in retail meat, storage and transformation of various fruits and vegetables, food fermentations, and storage of cabbage . Iberian hams from pigs reared under different conditions could be distinguished based on SIFT‐MS fingerprints, and microbial VOCs were used to identify microorganisms in various foodstuffs spoilage …”
Section: Introductionmentioning
confidence: 99%
“…Storage of shredded cabbage results in the formation of such volatiles, which can affect the cabbage aroma negatively or positively. SIFT‐MS analysis of shredded cabbage stored at different pHs and temperatures showed that storage at 25 °C produced significantly higher levels of off‐odours than storage at 4 °C. Low pH storage produced more of the desirable volatile allyl isothiocyanate, while high pH samples generated significantly higher concentrations of off‐odours such as dimethyl sulphide and dimethyl disulphide, indicating overall that low‐pH storage was more favourable.…”
Section: Current Applications Of Sift‐ms In Food Aroma Analysismentioning
confidence: 99%